Insecticidal activity of culture filtrates from liquid medium of Beauveria bassiana isolates from South Sumatra (Indonesia) wetland soil against larvae of Spodoptera litura - DWI RIZKI AYUDYA; Siti Herlinda; SUWANDI SUWANDI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Ayudya DR, Herlinda S, Suwandi S. 2019. Insecticidal activity of culture filtrates from liquid medium of Beauveria bassiana isolates from South Sumatra (Indonesia) wetland soil against larvae of Spodoptera litura. Biodiversitas 20: 2101-2109. The obstacle in utilizing entomopathogenic fungi to control pest insects in wetlands is the inability of their isolates to survive during the saprophytic phase due to the soil being very acidic. Therefore, the exploration of fungi being able to survive in the acidic soil was utilized in the acidic ecosystem. This study aimed to test the toxic activity of Beauveria bassiana culture filtrates from liquid medium at pH 2.5 and 6 against Spodoptera litura larvae. Total of ten isolates collected from South Sumatra, Indonesia was grown in liquid media at pH of 2.5 and 6 for six weeks. The result showed that the culture filtrate from liquid medium at pH 6 was more toxic against the larvae than that at pH 2.5. The mortality of the larvae at pH 6 reached 92%, while that at pH 2.5 it reached 13.33% only. The findings of present study revealed that the culture filtrate isolates of BPdR, BJgTs, BSwTd2, BSwTd3, BSwTd4, BKKPp2 from pH 2.5 media still caused high larvae mortality (6.67-13.33%). These seven isolates are superior due to their toxic nature at pH 2.5. Consequently, present study has increased the chances of success in utilizing these isolates for biological control in acidic ecosystems, such as peatlands, tidal lowlands, and freshwater swamps.